Semantic intrusion errors differentiate between amnestic MCI who are plasma p-tau217+ from p-tau217- after adjusting for initial learning strength - Rosie E. Curiel Cid; Rosie E. Curiel Cid; David Vaillancourt; David Vaillancourt; Alexandra Ortega; Alexandra Ortega; Elizabeth A. Crocco; Elizabeth A. Crocco; Kirsten Crenshaw; Kirsten Crenshaw; Stephanie M. Remedios; Breton M. Asken; et al. (Frontiers in Neurology)
BackgroundSemantic intrusion errors (SIEs) are associated with mild cognitive impairment (MCI) due to Alzheimer's disease (AD). It is unknown whether accounting for maximum learning capacity still leads to an increase in SIEs when elevated plasma p-tau217, a biological indicator of underlying AD, is present.MethodsOne hundred fifty-eight older adult participants completed the Loewenstein-Acevedo Scales for Semantic Interference and Learning (LASSI-L), a sensitive cognitive challenge test designed to elicit SIEs. Of these, 108 were clinically diagnosed with amnestic MCI (aMCI). Fifty-eight individuals met or exceeded a plasma p-tau217 positivity of >0.55 pg/ml, while 50 individuals scored below this threshold.ResultsAfter adjusting for demographic covariates and maximum learning capacity, the aMCI p-tau217+ group evidenced more SIEs compared to aMCI p-tau217- on the first (list B1; p = 0.035) and second trials of the competing list (list B2; p = 0.006). Biological predictors such as ApoE ε4 status, higher p-tau217, and older age were predictors of an elevated number of SIEs [list B2: F (3,104) = 10.92; p = 0.001; R = 0.489)].ConclusionsUnlike previous studies that used amyloid PET or other plasma biomarkers, individuals with aMCI p-tau217+ evidenced more SIEs, even after adjusting for their initial learning capacity, a covariate that has not been studied previously. These findings support that SIEs are more prevalent in the presence of underlying AD pathology and occur independent of learning deficits.